PRIORITY TASKS OF INCREASING THE COMPETITIVENESS OF THE ECONOMY OF UZBEKISTAN (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This article discusses the main ways to increase the volume of investments in the economy of our country and to create an investment environment.